MODEL REKAYASA PERILAKU MENGGUNAKAN INFORMASI AKUNTANSI BERBASIS AKRUAL PADA ORGANISASI PEMERINTAH - Agriyanto, Ratno (Jurnal Akuntansi dan Keuangan Indonesia, 2018)
This study uses the theory of planned behavior, cognitive theory and theory of expectation to test the determinants of behavior using accrual basis accounting information. This study uses 147 respondents of local government financial managers in Semarang City and Banyumas Regency. The result of this research shows that trust has positive effect on attitude. Behavior, subjective norms and perceived control behaviors also positively influence the intention in using accrual basis accounting information. Intention and perceived behavior controls positively affect the behavior of using accrual basis accounting information. The results also show that Intolerance of Ambiguity weakens the influence of intention on behavior, while accounting performance based reward strengthens the influence of intention on behavior. The practical implications of the research can be used by governments as behavioral engineering strategies using accrual basis accounting information. The practical implications of the research can be as behavioral engineering strategies using accrual basis accounting information on government organizations.